“A living lab within a lab”: approaches and challenges for scaling digital public health in resource-constrained settings - Mukherjee, Arunima S.; Sahay, Sundeep; Kumar, Rajesh; Banta, Rashi; Joshi, Neha (Frontiers in Public Health, 2023)
A living lab is an emerging concept, particularly in Europe, as a vehicle to develop digital innovations through a process of co-produced design and development, which takes place, physically and socially, in real-life use contexts. However, there is limited research relating to guiding our understanding of the process by which such labs are established, and digital innovations are co-created and scaled to other settings requiring similar solutions. Furthermore, beyond Europe, the concept of a living lab has not found widespread application in low- and middle-income countries (LMICs), particularly in their public health contexts. Public health systems offer the unique scaling challenge of “all or nothing”, implying that data are required from the whole population rather than isolated pilot settings. The living lab approach promises the rich potential to strengthen public systems but comes with twin interconnected challenges. First, for building appropriate digital solutions to address local public health challenges, and second, in scaling them to other public health facilities. This article investigates these twin challenges through ongoing empirical work in India and identifies three key domains of analysis, which are as follows: the first concerns the process of establishing an enabling structure of a “living lab within a lab”; the second concerns leveraging the capabilities offered by free and open-source digital technologies; and the third concerns the driving impetus to scaling through agile and co-constructed technical support.